Injected Human Muscle Precursor Cells Overexpressing PGC-1α Enhance Functional Muscle Regeneration after Trauma - Deana Haralampieva; Souzan Salemi; Thomas Betzel; Ivana Dinulovic; Stefanie D. Krämer; Roger Schibli; Tullio Sulser; Christoph Handschin; Simon M. Ametamey; Daniel Eberli (Stem Cells International)
While many groups demonstrated new muscle tissue formation after muscle precursor cell (MPC) injection, the capacity of these cells to heal muscle damage, for example, sphincter in stress urinary incontinence, in long-term is still limited. Therefore, the first goal of our project was to optimize the functional regenerative potential of hMPC by genetic modification to overexpress human peroxisome proliferator-activated receptor gamma coactivator 1-alpha (hPGC-1α), key regulator of exercise-mediated adaptation. Moreover, we aimed at establishing a feasible methodology for noninvasive PET visualization of implanted cells and their microenvironment in muscle crush injury model. PGC-1α-bioengineered muscles showed enhanced marker expression for myogenesis (α-actinin, MyHC, and Desmin), vascularization (VEGF), neuronal (ACHE), and mitochondrial (COXIV) activity. Consistently, use of hPGC-1α_hMPCs produced significantly increased contractile force one to three weeks postinjury. PET imaging showed distinct differences in radiotracer signals ([18F]Fallypride and [11C]Raclopride (both targeting dopamine 2 receptors (D2R)) and [64Cu]NODAGA-RGD (targeting neovascularization)) between GFP_hMPCs and hD2R_hPGC-1α_hMPCs. After muscle harvesting, inflammation levels were in parallel to radiotracer uptake amount, with significantly lower uptake in hPGC-1α overexpressing samples. In summary, we facilitated early functional muscle tissue regeneration, introducing a novel approach to improve skeletal muscle regeneration. Besides successful tracking of hMPCs in muscle crush injuries, we showed that in high-inflammation areas, the specificity of radioligands might be significantly reduced, addressing a possible bottleneck of neovascularization PET imaging.